Ionizing radiation leads to exosome secretion in macrophages through MYC-mediated pathways - Hanui Lee; Gyeong Han Jeong; Geun-Joong Kim; Seung Sik Lee; Byung Yeoup Chung; Hyoung-Woo Bai (PLoS ONE, 2025)
Exosomes are cell-derived vesicles that play a crucial role in intracellular communication and are promising biomarkers for therapeutic applications. Despite their significant potential, the application of exosomes as biological therapeutics is limited by their low yield and inconsistent production quality. Ionizing radiation is known to enhance exosome release; however, this effect has been primarily studied in cancer cells. Given the critical role of macrophages in immune regulation and their potential for exosome-based therapies, we investigated the impact of gamma radiation on the secretion of macrophage-derived exosomes. This study demonstrated that gamma radiation significantly enhanced exosome release by both naïve and polarized macrophages. This effect was associated with the overexpression of Myh10 and Myo5b, the motor proteins that play crucial roles in exosome biogenesis and secretion. Furthermore, RNA sequencing and western blot analyses identified the EGFR/IGFR-MYC signaling axis as a key upstream pathway regulating the expression of Myh10 and Myo5b, thereby accelerating exosome secretion. These findings provide a deeper understanding of the molecular mechanisms underlying radiation-induced exosome secretion from macrophages and offer a novel strategy for optimizing exosome production to advance exosome-based therapeutic applications.